Nucleation and growth of lattice crystals - Braides, Andrea; Scilla, Giovanni; Tribuzio, Antonio (Journal of nonlinear science, 2021)
A variational lattice model is proposed to define an evolution of sets from a single point (nucleation) following a criterion of “maximization” of the perimeter. At a discrete level, the evolution has a “checkerboard” structure and its shape is affected by the choice of the norm defining the dissipation term. For every choice of the scales, the convergence of the discrete scheme to a family of expanding sets with constant velocity is proved.